Understanding and Supporting Twice-Exceptional Students: The Role of Educational Professionals in Promoting Inclusive Practices - Mithans, Monika; Tivadar, Jasna; Ograjšek, Sabina (Selected Contemporary Research on Special Needs, Giftedness, and Talent in Slovenia, 2025)
In the following chapter, the discussion centres on twice-exceptional students, who are recognized for their unique combination of gifted abilities and special educational needs The research conducted for this study focuses on the prevalence of misconceptions among education professionals and the challenges they face in identifying and working with this group of students. The findings reveal a significant level of awareness among professionals about the complexity of giftedness and special educational needs while pointing out certain misconceptions. Additionally, the overall results collectively point to a strong awareness of the challenges related to twice-exceptionality, highlighting the critical need to address particular deficits and provide individualized support. The diversity of responses by the research participants indicates varying perspectives on how these challenges manifest and how they should be addressed. Moreover, the results indicate that educators familiar with the concept of twice-exceptionality are better equipped to identify the unique needs of twice-exceptional students and are less prone to misconceptions. Finally, the chapter highlights the critical role of further education and training for professionals to improve inclusivity and the success of twice-exceptional students.